2015
DOI: 10.1002/pmic.201400502
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profile of the plant‐pathogenic oomycete Phytophthora capsici in response to the fungicide pyrimorph

Abstract: Pyrimorph is a novel fungicide from the carboxylic acid amide (CAA) family used to control plant-pathogenic oomycetes such as Phytophthora capsici. The proteomic response of P. capsici to pyrimorph was investigated using the iTRAQ technology to determine the target site of the fungicide and potential biomarker candidates of drug efficacy. A total of 1336 unique proteins were identified from the mycelium of wild-type P. capsici isolate (Hd3) and two pyrimorph-resistant mutants (R3-1 and R3-2) grown in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 63 publications
3
45
0
Order By: Relevance
“…Biological processes with particular functions have been identified using proteomic analyses in previous studies of agriculturally important plants and animals262728. In the present study, the proteomic profile of the LD muscle of two indigenous Chinese pig breeds and two pig breeds introduced into China were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Biological processes with particular functions have been identified using proteomic analyses in previous studies of agriculturally important plants and animals262728. In the present study, the proteomic profile of the LD muscle of two indigenous Chinese pig breeds and two pig breeds introduced into China were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the influences of the different oestrus seasons and the FecB gene on ovarian structure and function remain unclear. Proteomics have been widely used in agricultural research, in order to explore the potential processes with particular functions212223. To get a further understanding of the molecular mechanism for the high prolificacy of Small Tail Han sheep, we applied an iTRAQ based comparative proteomic strategy to quantitatively identify the DEPs between Dorset sheep (Dorset), Small Tail Han sheep with FecB mutation (Han BB) and Han sheep without FecB mutation (Han ++).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current research focuses on the relationship between the enzyme gene or structure of the compound and fungicidalicidal activity to explain the fungicide mechanism or to synthesize new fungicides. However, the three‐dimensional structure (3‐DS) of its cellulose synthase (CesA3) is not well studied and the related research has great research value given its importance to discover or develop new fungicide . A recent study isolated and identified the CesA3 gene of multiple oomycete species, elucidating the phylogenetic basis and potential molecular mechanisms of sensitivity and tolerance of cellulose synthase 3 (CesA3) to carboxylic acid amide fungicides.…”
Section: Introductionmentioning
confidence: 99%